2002
DOI: 10.5172/conu.13.2-3.259
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of primary care services provided by nurses' private clinics in Thailand

Abstract: The purpose of this descriptive study was to determine the cost-effectiveness of primary care provided at nurses' private clinics in Thailand. The sample consisted of 63 nurses' private clinics and 3518 clients. These clinics were selected by multi-stage random sampling. An observation sheet and three questionnaires were used to collect the data. The data indicated that Nurses' private clinics can provide services for about 90% of the clients' problem at the primary care level at about a 50% lower cost than ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…; Hanucharurnkul et al. ; Presley ). In the USA, NP private practices have been established in retail clinics within shopping centres, rural health clinics and Nurse Managed Health Centres (NMHC; Hansen‐Turton et al.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…; Hanucharurnkul et al. ; Presley ). In the USA, NP private practices have been established in retail clinics within shopping centres, rural health clinics and Nurse Managed Health Centres (NMHC; Hansen‐Turton et al.…”
Section: Discussionmentioning
confidence: 99%
“…In Thailand, the private model is also community based, with nurse‐led private clinics established in remote communities that would otherwise have limited access to health care (Hanucharurnkul et al. ). It is unclear what proportion of these nurse‐led clinics is run by NPs; research showed that 8% were qualified to Masters level and 87% to Baccalaureate level (Hanucharurnkul et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations